2009
DOI: 10.1002/app.30182
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of polymers from soybean oil and p‐dinitrosobenzene

Abstract: In this study, rubbery, bio-based thermoset polymers were synthesized from soybean oil (SO) and pdinitrosobenzene (DNB) via an ene reaction. Polymeric pdinitrosobenzene (PDNB) was synthesized from p-quinone dioxime and was thermally depolymerized in the presence of SO. SO/PDNB polymers were synthesized by a twostage polymerization. During the reaction, the role of different parameters such as mol ratio of SO and PDNB, preheating temperature of SO, polymerization time, and temperature were examined. Polymerizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…This crucial feature is of great interest because most of the time, the oxidized version of the quinone, for example, is generally soluble and leads to a loss of capacity. The presence of a polymer in the oxidized state should make it possible to avoid such phenomena . NMR spectrum of PNND showed the disappearance of hydroxide peak at 12.10 ppm.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This crucial feature is of great interest because most of the time, the oxidized version of the quinone, for example, is generally soluble and leads to a loss of capacity. The presence of a polymer in the oxidized state should make it possible to avoid such phenomena . NMR spectrum of PNND showed the disappearance of hydroxide peak at 12.10 ppm.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of a polymer in the oxidised state should make it possible to avoid such phenomena. 18 NMR spectrum of PNND showed the disappearance of hydroxide peak at 12.10 ppm. Moreover, all the other peaks were shifted to upfield, from 7.85-6.44 ppm to 7.23-6.65 ppm, for the presence of O-N=N-O group (Figure S5).…”
Section: Resultsmentioning
confidence: 99%
“…[283] The tribological properties of brake pads were significantly enhanced by the addition of RS and rice husk dust into the composites. [284] In another study, the friction coefficient and wear rate of chopped sugar cane fiber reinforced polyester (CSCRP) were compared with those of chopped glass fiber reinforced polyester (C-GRP) composites at different lengths of fiber. For 1 mm of fiber it was found that the wear rate of CSCRP composites was nearly 10 times higher than C-GRP composites.…”
Section: Tribological Propertiesmentioning
confidence: 99%
“…21 Additionally, certain nitroso compounds are low-temperature structuring agents to produce of synthetic rubbers. 22 Furthermore, a number of review papers have been devoted to computations, chemistry and applications of C -nitroso compounds. 22 a ,23…”
Section: Introductionmentioning
confidence: 99%